Greening the Maple Canadian Ecocriticism in Context - Soper, Ella; Bradley, Nicholas (Energy, Ecology, and the Environment, 2013)
Ecocriticism can be described in very general terms as the investigation of the many ways in which culture and the environment are interrelated and conceptualized. Ecocriticism aspires to understand and often to celebrate the natural world, yet it does so indirectly by focusing primarily on written texts. Hailed as one of the most timely and provocative developments in literary and cultural studies of recent decades, it has also been greeted with bewilderment or scepticism by those for whom its aims and methods are unclear. This book seeks to bring into view the development of ecocriticism in the context of Canadian literary studies. Selections include work by Margaret Atwood, Northrop Frye, Sherrill Grace, and Rosemary Sullivan.